ИРГЭНИЙ НИЙГЭМ ҮНДЭСНИЙ АЮУЛГҮЙ БАЙДЛЫГ ХАНГАХ СУБЬЕКТ МӨН: ОХУ, АНУ-ЫН ТУРШЛАГА - Нэргүй, Б (Proceedings of the Mongolian Academy of Sciences, 2016)
Abstract: A civil society in the security sector is main element of social reform. One of the important issues of the civil society in the security sector in the democratic society is to be increased the participation of “civil society” in the development and implementation process of the national security and defense policy. Civil society is composed of the totality of many voluntary social relationships, civic and social organizations, and institutions that form of the basis of functional society, as distinct from the force-backed structures of the state. The civil society would not be opposed to the state. The activities and operations of the civil society might be possible to implement in the situations of the democratic society relations, in regarding too basis of the strengthened basement of the civil society establishment. Accordingly, that civil society is possible to develop elsewhere, that would be established strengthening possibility. Otherwise a civil society was developed elusively, when that is placed by the concurrence authoritarian and totalitarian condition. Civil society activities as subject provides different impact on ensure safety academic papers are a new area of security studies. Civil society’s participation in the security sector’s learning from the experience of the United States and Russia.